Analysis Of Civil Legal Responsibility Of Dangerous Skincare Sellers Towards Consumers (Case Study Of The Distribution Of Pinkflash Brand Cosmetics In Bengkulu) - Prima Ramadhania; Hurairah Hurairah; Sandi Aprianto (JURNAL HUKUM SEHASEN, 2026)
The circulation of cosmetic and skincare products that do not meet safety standards remains a serious problem in consumer protection. One example is the Pinkflash brand of cosmetics, whose distribution permit has been revoked by the Food and Drug Monitoring Agency (BPOM), yet it is still found circulating on the market and causing harm to consumers. This study aims to analyze the civil legal liability of sellers to consumers for the distribution of hazardous cosmetics and the legal protection efforts for harmed consumers. The research method used is empirical legal research with a statutory and case-based approach. Data were obtained through literature review and interviews, then analyzed qualitatively. The results indicate that sellers who continue to distribute hazardous cosmetics are civilly liable for consumer losses under Law Number 8 of 1999 concerning Consumer Protection and Article 1365 of the Civil Code. Legal protection for consumers can be achieved through the role of BPOM, consumer dispute resolution, and civil lawsuits in court.